Associations Between General Perceptions of COVID-19 and Posttraumatic Stress Disorder in Korean Hospital Workers: Effect Modification by Previous Middle East Respiratory Syndrome Coronavirus Experience and Occupational Type - Youngrong Lee (Journal of Preventive Medicine and Public Health, 2021)
Objectives This study investigated associations between perceptions of coronavirus disease 2019 (COVID-19) and the prevalence of posttraumatic stress disorder (PTSD) in workers at hospitals designated to treat COVID-19, as well as the difference in the magnitude of these associations by occupational type and previous Middle East respiratory syndrome coronavirus (MERS-CoV) experience. Methods The participants were workers at hospitals designated to treat COVID-19 who completed a questionnaire about their perceptions related to COVID-19, work experience during the previous MERS-CoV outbreak, and symptoms of PTSD ascertained by the PTSD Checklist for the Diagnostic and Statistical Manual of Mental Disorders. Participants’ characteristics were compared using the chi-square test. Multivariable logistic regression was performed to evaluate the associations between perceptions and the prevalence of PTSD, stratified by occupational type and previous MERS-CoV experience. Results Non-medical personnel showed stronger associations with PTSD than medical personnel according to general fear (odds ratio [OR], 6.67; 95% confidence interval [CI], 1.92 to 23.20), shortages of supplies (OR, 1.29; 95% CI, 1.07 to 1.56), and issue-specific fear (OR, 1.29; 95% CI, 1.05 to 1.59). Those with prior MERS-CoV quarantine experience were more prone to PTSD than those without such experience in terms of general fear (OR, 1.70; 95% CI, 1.22 to 2.37), shortages of supplies (OR, 1.24; 95% CI, 1.10 to 1.40), and issue-specific fear (OR, 1.21; 95% CI, 1.06 to 1.38). Conclusions During the COVID-19 pandemic, non-medical personnel tended to have higher odds of being categorized as having PTSD. Workers with prior MERS-CoV experience were more susceptible than those without such experience. These findings suggest the need for timely interventions to manage human resources for a sustainable quarantine system.